The Math Mindset: How Master Business Students' Attitudes Impact Their Academic Success - Pokharel, Thakur Prasad (Journal of Business and Management, 2025)
Background: Math mindset of business students seeks to understand how students perceive the role of mathematics in quantitative subjects such as accounting, finance, economics, auditing, and budgeting.Objectives: The objective of this study is to examine the role of selfconfidence, value, motivation, and enjoyment of mathematics in achieving success in business studies. This investigation aims to explore students' belief systems regarding the independent and dependents variables.Methods: This study applied descriptive and analytical survey research design. A total of 265 respondents from MBA and MBS programs at various universities and colleges within the Pokhara Valley were purposively selected. Primary data was collected through field visits. The survey included nine demographic questions and 31 structured items. The reliability of the instrument was verified using Cronbach’s alpha. Data analysis was made using descriptive and inferential statistics.Results: This study has found a positive correlation between success in business studies and independents variables such as self-confidence, value, motivation, and enjoyment of mathematics. It has been revealed that the value of mathematics and motivations towards mathematics have a significant impact on success in business studies at the master's level. Mathematics is recognized as highly useful and relevant to their future academic and professional careers. Furthermore, more than 80% of students have expressed the need for additional mathematics classes during their study time.Conclusion: The motivations towards mathematics and value of mathematics have significantly influenced outcomes in university-level management studies. The majority of learners have indicated a need for additional mathematics support during their studies. This suggests that admission criteria could be revised to make mathematics a compulsory subject at the school level. New learners can be guided and motivated to apply mathematical knowledge to real-life situations. Further research is needed to explore the cause-and-effect relationship between business students' attitudes toward mathematics and their success in business studies across different colleges, periods, and locations, to validate and generalize these findings.JEL Classification: C20, C40, C70